Listeria monocytogenes Illness and Deaths Associated With Ongoing Contamination of a Multiregional Brand of Ice Cream Products, United States, 2010–2015. (7th July 2022) - Conrad, Amanda R; Tubach, Sheri; Cantu, Venessa; Webb, Lindsey Martin; Stroika, Steven; Moris, Steve; Davis, Megan; Hunt, D Charles; Bradley, Kristy K; Kucerova, Zuzana; Strain, Errol; Doyle, Matthew; et al.
Abstract: Background: Frozen foods have rarely been linked to Listeria monocytogenes illness. We describe an outbreak investigation prompted by both hospital clustering of illnesses and product testing. Methods: We identified outbreak-associated listeriosis cases using whole-genome sequencing (WGS), product testing results, and epidemiologic linkage to cases in the same Kansas hospital. We reviewed hospital medical and dietary records, product invoices, and molecular subtyping results. Federal and state officials tested product and environmental samples for L. monocytogenes . Results: Kansas officials were investigating 5 cases of listeriosis at a single hospital when, simultaneously, unrelated sampling for a study in South Carolina identified L. monocytogenes in Company A ice cream products made in Texas. Isolates from 4 patients and Company A products were closely related by WGS, and the 4 patients with known exposures had consumed milkshakes made with Company A ice cream while hospitalized. Further testing identified L. monocytogenes in ice cream produced in a second Company A production facility in Oklahoma; these isolates were closely related by WGS to those from 5 patients in 3 other states. These 10 illnesses, involving 3 deaths, occurred from 2010 through 2015. Company A ultimately recalled all products. Conclusions: In this US outbreak of listeriosis linked to a widely distributed brand of ice cream, WGS and product sampling helped link cases spanning 5 years to 2 production facilities, indicating longstanding contamination. Comprehensive sanitation controls and environmental and product testing for L. monocytogenes with regulatory oversight should be implemented for ice cream production. Abstract : Whole-genome sequencing, paired with epidemiologic data, identified commercially produced ice cream products as the source of a high-profile listeriosis outbreak that involved 10 cases over 5 years.